EFEKTIVITAS LAYANAN INFORMASI MODEL SOSIODRAMA TERINTEGRASI PEMBELAJARAN PKN UNTUK MEREDUKSI PERILAKU AGRESIF DI SEKOLAH DASAR - Opi Andriani (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research was motivated by the existence of students who carried out verbal, physical and psychological violence towards aggressiveness with a high tendency. This aggressive behavior in the world of education is very risky for students' academic activities psychologically at school for both the perpetrator and the victim. This research aims to reveal the effectiveness information services model sociodrama integrated for Civics learning to reduce students' aggressive behavior in elementary schools. This type of research is a Quasi Experiment using a One Group Pretest-Posttest Design on research design. The subjects in this research were 15 students in grades V and VI of SD Negeri 196 Taman Agung, Bungo Regency, who were selected using purposive sampling techniques. The data collection technique in this research was a Likert scale model questionnaire used in the pre-test and post-test. Based on the distribution table data in the experimental group, there was a decrease in scores from 66.63 to 53.2. Furthermore, based on the t-test, the use of integrated sociodrama model information services for Civics lessons was declared effective in reducing aggressive behavior in elementary schools. This is proven by the results of the difference test value (t) from the calculation which shows that tcount is 5.662 while ttable is 2.160. so that if we enter it into the hypothesis formula tcount > ttable it can be concluded that Ho is rejected and Ha is accepted.